Youth and political trust in the European Parliament: the potential of social media communication - Moreno-Cabanillas, Andrea; Serna-Ortega, Álvaro; Almansa-Martínez, Ana (Estudios sobre el Mensaje Periodístico, 2026)
The crisis of political trust among young citizens in the institutions of the European Union is one of the main challenges that must be addressed in order to guarantee the future legitimacy of the EU project. This research aims to find solutions to this problem through communication on social media and has two objectives: to analyze the influence of sociodemographic variables on young citizens' political trust in the European Parliament and to identify the types of communication on the European Parliament's social media that they perceive as having the greatest potential to improve political trust in the institution. The study adopts a quantitative methodological approach. Data collection includes N=470 questionnaires completed by young citizens aged 18 to 26 living in Germany, France, Italy, Spain, and Poland. The data analysis is carried out using statistical procedures such as descriptive analyses, a binary logistic regression model, an analysis of the model's B regression coefficients, an ordinal regression, a Kruskal-Wallis test, and a Dunn post-hoc test with Bonferroni correction. The results indicate that the influential sociodemographic variables are socioeconomic status, employment status, and educational level. In addition, it is observed that the types of social media communications with the greatest perceived potential are those that involve bidirectionality. These findings are useful for designing communication strategies on the European Parliament's social media aimed at improving its trust among European youth, both in terms of audience and content.
Keywords: communication; political trust; youth; social media; transparency; European Union